Development of composite catalyst containing renewable biochar blended with zinc oxide and copper diphenyl amine for visible light photocatalytic degradation of methylene blue - Saif, Aroosha; Rizvi, Syeda Itrat; Shaukat, Zarneen; Saif, Mamoona; Tabassum, Sobia; Khalid, Rizwan; Javed, Fahad; Rebouh, Nazih Y.; Hassan, Faiza; Zaman, Qamar uz (Frontiers in Sustainable Food Systems, 2025)
IntroductionEffective wastewater management remains a significant challenge in Pakistan, with conventional methods often falling short in addressing the release of harmful pollutants into water bodies.MethodThis study explores the use of a novel composite photocatalyst combining biochar, zinc oxide (ZnO), and copper diphenylamine (Cu-DPA) to improve wastewater treatment under visible light. The composite was prepared by varying the Cu-DPA content in ZnO, with ratios of 50%, 40%, 30%, and 17%, alongside standard biochar ZnO and Cu-DPA formulations. Characterization techniques, including FTIR, XRD, and UV-visible spectroscopy were used to analyze the composite's properties. Photocatalytic performance was assessed by degrading Methylene Blue, a common dye pollutant, under visible light.ResultsThe results showed that while ZnO alone achieved 78% degradation, the composites with different Cu-DPA ratios demonstrated varying efficiencies, with the biochar-enhanced ZnO/Cu-DPA composite achieving the highest degradation rate of 97% in 80 min.DiscussionThis composite exhibited good reusability over seven cycles. This research highlights the potential of the biochar ZnO/Cu-DPA composite as an effective, eco-friendly solution for wastewater treatment, offering significant improvements in photocatalytic performance and sustainability.